New evaluation framework for human-assistive devices based on humanoid robotics. (17th April 2016) - Ayusawa, Ko; Yoshida, Eiichi; Imamura, Yumeko; Tanaka, Takayuki
Abstract : This paper presents the new application of a humanoid robot as an evaluator of human-assistive devices. The reliable and objective evaluation framework for assistive devices is necessary for making industrial standards in order that those devices are used in various applications. In this framework, we utilize a recent humanoid robot with its high similarity to humans, human motion retargeting techniques to a humanoid robot, and identification techniques of robot's mechanical properties. We also show two approaches to estimate supporting torques from the sensor data, which can be used properly according to the situations. With the general formulation of the wire-driven multi-body system, the supporting torque of passive assistive devices is also formulated. We evaluate a passive assistive wear 'Smart Suit Lite (SSL)' as an example of device, and use HRP-4 as the humanoid platform. Graphical Abstract: